ORNAMENTAL BEAUTY IN MĀLAVIKĀGNIMITRAM : AN ANALYTICAL STUDY - Ray, Mukul Chandra (Journal of Creativity in Art and Design, 2026)
Mālavikāgnimitram, one of Kālidāsa’s early theatrical works, is known for its elegant portrayal of courtly love and refined aesthetic sense. This research examines the ornamental beauty (alaṁkāra-śobhā) of the text, emphasizing how poetic figures enhance the dramatic texture. This study analyzes the use of śabdālaṁkāras (figures of sound) and arthālaṁkāras (figures of sense) in verses and dialogues to evoke rasa, specifically śṛṅgāra. According to the study, the drama’s visual refinement stems not just from its plot but also from its sophisticated use of poetic embellishment, which adds emotional depth and artistic appeal.